Improved water supply in the Ghanaian Volta Basin: who uses it and who participates in community decision-making? - Engel, Stefanie; Iskandarani, Maria; Useche, Maria del Pilar (International Food Policy Research Institute, 2005)
We examine access to, use of, and participation in decisions on improved water supply in the Volta basin of Ghana, one of the first countries to introduce a community-based approach to rural water supply on a large scale. While 71 percent of the households interviewed have access to improved water, 43 percent of these continue to use unsafe sources as their main domestic water source. Our results indicate that quality perceptions and opportunity costs play an important role in households’ choice of water source. The effect of prices and income levels on this choice differs according to the pricing system used.